Potential Irregularities in Arrangements of Amendment Regarding the Term of Office of Village Heads in the Indonesian Constitutional Law System - Mahardika, Ahmad Gelora (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The discourse to extend the term of office of the village head creates problems in the Indonesian constitutional system. This is because the addition will potentially extend the term of office of the village head to 27 (twenty-seven) years. In fact, cumulatively, the term of office of the village head based on Law Number 6 of 2014 concerning Villages is quite long, namely 6 (six) years and can be elected 3 (three) times, which means that the village head can serve 18 (eighteen) year. On the other hand, the duration of a village head, which has the potential to reach 18 years, is also essentially inconsistent with democratic principles which provide a maximum limit for public officials who are elected through political mechanisms to hold office. For this reason, the idea of reconstructing the village head's term of office has become an urgent issue in the Indonesian constitutional system. The research question in this article is whether there is a potential for irregularities in the arrangements regarding the extension of the village head's term of office. The type and research approach used in this article is comparative normative juridical research with a statutory approach. The hypothesis in this article is that the long term of office of the village head is contrary to the concept of democracy, namely the limitation of power.